AGE-SPECIFIC DIFFERENCES IN PROJECT SELECTION - Gulnara Mamadzhanovna Israilova, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This work demonstrates age-specific differences in project selection. The use of project-based learning in Russian language and literature lessons enables the development of new forms of student organization and significantly contributes to improving the quality of student learning. In our lessons, we teach children to think independently,  identify,  and  solve  problems,  drawing  on  knowledge  from  various fields, and develop their ability to establish cause-and-effect relationships.